2009
DOI: 10.2337/db09-0166
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinal Neurodegeneration Is Associated With Mitochondrial Oxidative Stress and Is Improved by an Angiotensin Receptor Blocker in a Model Combining Hypertension and Diabetes

Abstract: OBJECTIVE-Diabetic retinopathy displays the features of a neurodegenerative disease. Oxidative stress is involved in the pathogenesis of diabetic retinopathy. This investigation sought to determine whether hypertension exacerbates the oxidative stress, neurodegeneration, and mitochondrial dysfunction that exists in diabetic retinopathy and whether these changes could be minimized by the angiotensin II type 1 (AT 1 ) receptor blocker (ARB) losartan.RESEARCH DESIGN AND METHODS-Diabetes was induced in spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 46 publications
3
64
0
3
Order By: Relevance
“…ACE inhibition and ARB improve aspects of neuronal and glial damage in both situations [42], such as ameliorating losses in the electroretinogram [25,38,43] and neuronal and glial cell degeneration [44][45][46]. Our identification of renin in retinal Müller cells [2] and ganglion cells [3] is suggestive that aliskiren may influence these cell populations.…”
Section: Discussionmentioning
confidence: 83%
“…ACE inhibition and ARB improve aspects of neuronal and glial damage in both situations [42], such as ameliorating losses in the electroretinogram [25,38,43] and neuronal and glial cell degeneration [44][45][46]. Our identification of renin in retinal Müller cells [2] and ganglion cells [3] is suggestive that aliskiren may influence these cell populations.…”
Section: Discussionmentioning
confidence: 83%
“…155 Consumption of dark chocolate is associated with blood pressure reduction associated with a reduction in oxidative stress and increase in nitric oxide bioavailability, 156 both abnormalities that have been involved in the pathogenesis of diabetic nephropathy and retinopathy. 67,[85][86][87][88][93][94][95][97][98][99]156 Finally, in experimental diabetes, the use of green tea was associated with an improvement in diabetic nephropathy and retinopathy and associated with a reduction in oxidative stress. 91, 157 The usefulness of these dietary approaches in diabetic patients with hypertension and nephropathy or retinopathy that are on standard treatment deserves to be tested in larger clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…Experimental and clinical studies have demonstrated that these maneuvers are also able to reduce superoxide generation and/or increase anti-oxidant defenses. 98,99,148,149 In this review, we have provided evidence that local generation of oxidative stress and inflammation can be a common mechanism of renal and retinal lesion in the presence of diabetes and hypertension. Although efficient, blood glucose control, normalization of arterial pressure and drugs that interfere in RAAS are currently unable to completely arrest diabetic renal and retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations